Frying the fish - Mumbai Archive Project Team (Jio Institute, 2024)
Frying is the last step of preparation. The marinated fish are put one at a time in boiling oil. They are fried until they become crispy and golden brown on both sides. Depending on how it is prepared, the fish can also be grilled, roasted, smoked, or barbecued.